Bourdieu e a educação: formação de doutores e trajetórias acadêmicas de doutorandos orientados por pesquisadoras brasileiras - Barrios, Rogério (2023)
This thesis aimed to investigate the academic formation and career trajectories of educators who completed their doctoral studies in public education programs, under the guidance of three renowned researchers who served as qualified interpreters of the theoretical contributions of the French sociologist Pierre Bourdieu. The scope of this study was to analyze the similarities and differences in academic formation, focusing on doctoral theses, as well as educational trajectories based on the positions held before and after completing their doctorates. The study was grounded in Bourdieu's General Theory of Fields, particularly the Scientific Field. The selected researchers were Denice Bárbara Catani (USP), Ione Ribeiro Valle (UFSC), and Maria Alice Nogueira (UFMG). Among all the doctoral students mentored by these researchers, thirty academic theses were selected for analysis because they explicitly referenced the use of Bourdieu as a theoretical source in their abstracts. This allowed for the synthesis and analysis